Revitalization of Local Language in Si Bolang - Rahmayanti, Indah; Hawa, Anni Malihatul; Nofiyanti, Fifi (TALENTA Publisher, 2022)
The millennial era and the times have made language change. Not only language but even ethics, manners, and habits change. Indonesians are more interested in films, YouTube, and social media. The existence of Si Bolang shows that highlighting children's activities in the area can be a way to preserve the language. These shows often use regional languages during the dialogue between the character Si Bolang and the local children. In this study, he wanted to know about the revitalization of extinct languages in the 2019 Si Bolang program for language preservation. The research method used is descriptive qualitative. In the research, watching Si Bolang shows in 2019 by selecting 3 shows, then looking for the revitalization of the extinct languages contained in these shows. The results showed that the Si Bolang version shows